(untitled) - Mishchenko, Michael I. (Cambridge, 2002)
This thorough and up-to-date treatment first introduces the general formalism of scattering, absorption, and emission of light and other electromagnetic radiation by arbitrarily shaped and arbitrarily oriented particles. It then discusses the relation of the radiative transfer theory to single-scattering solutions of Maxwell's equations and describes in detail exact theoretical methods and computer codes for calculating scattering, absorption, and emission properties of arbitrarily shaped particles. Further chapters demonstrate how scattering and absorption characteristics of small particles depend on particle size, refractive index, shape, and orientation. The work illustrates how the high efficiency and accuracy of existing theoretical and experimental techniques, and the availability of fast scientific workstations, result in advanced physically-based applications of electromagnetic scattering to non-invasive particle characterization and remote sensing. This book will be valuable for science professionals, engineers and graduate students in a wide range of disciplines including optics, electromagnetics, remote sensing, climate research, and biomedicine.
Keywords: Electromagnetic waves,Particles,Sóng điện từ,Các hạt; Scattering,Optical properties,Tán xạ,Tính chất quang học